Blockchain as urban governance infrastructure in private cities: an exploratory review - Dehouche, Nassim (Frontiers in Sustainable Cities, 2025)
Private city models—encompassing Charter Cities, Free Private Cities, Seasteads, Startup Cities, and Special Economic Zones (SEZs)—are emerging as innovative alternatives to traditional urban governance. This article examines the discussion of these private urban experiments through the lens of blockchain technology and cryptocurrency. We present a structured taxonomy of private city models and analyze case studies to illustrate how blockchain can facilitate governance, economic transactions, and transparency in these contexts. Drawing on peer-reviewed literature, we examine how distributed ledger technologies enable new forms of decentralized governance and finance (e.g., local cryptocurrencies and decentralized finance for city services) while also identifying critical challenges and limitations. Comparisons with traditional public-sector urban governance highlight the potential efficiency gains and transparency improvements of blockchain-powered private cities, as well as concerns regarding accountability, inclusivity, and regulatory integration. Finally, we discuss future prospects for integrating blockchain in urban development, including the concept of networked “crypto cities,” and outline key areas for further research. The analysis balances theoretical propositions with empirical insights, ultimately finding that blockchain can augment private city models by enhancing transparency and enabling novel economic systems, but it is not a panacea for governance and must be implemented with careful consideration of social and legal frameworks.